College student mental health risks during the COVID-19 pandemic: Implications of campus relocation. (April 2021) - Conrad, Rachel C.; Hahm, Hyeouk "Chris"; Koire, Amanda; Pinder-Amaker, Stephanie; Liu, Cindy H.
Abstract: Purpose: During the COVID-19 pandemic, many universities evacuated their campuses, requiring students to vacate on campus residences. The psychological outcomes of students who relocated during the pandemic remains unknown. We examined mandated relocation experiences related to self-reported worry, grief, loneliness, and depressive, generalized anxiety, and post-traumatic stress disorder (PTSD) symptoms among college students during the COVID-19 pandemic. Methods: We analyzed cross-sectional survey data obtained from April 9 to August 4, 2020 on 791 young adults (ages 18–30 years) who were enrolled at a U.S. university. The CARES 2020 Project (COVID-19 Adult Resilience Experiences Study) is an online survey of young adults' mental health during the COVID-19 pandemic. Recruitment relied on snowball sampling. Participants were asked if they were required to relocate from campus and among those who did, their experiences in moving. COVID-19-related worry and grief, loneliness, and depressive, anxiety, and PTSD symptoms were assessed. Results: Approximately one-third of students reported being mandated to relocate. Students mandated to relocate reported more COVID-19-related grief, loneliness, and generalized anxiety symptoms compared to those who did not even after controlling for the severity level of local COVID-19 outbreaks. Students who had to leave behind valuable personal belongings reported more COVID-19-related worries, grief, and depressive, generalized anxiety, and PTSD symptoms. Conclusions: Students who were mandated to relocate reported worse psychological outcomes compared to students who were not mandated to relocate. Our findings have implications for addressing the psychological impact of evacuating college campuses during public health emergencies and other disasters.